Transitions in Latin America and in Poland and Syria - Zarembka, Paul (Emerald, 2007)
The research is founded on analyzing society in a manner consistent with classical Marxism. International in scope, the annual volumes deal primarily with economic and political issues and the unity between them. Both theoretical and empirical works are included. While published papers must be appropriate for developing class analysis of society, they need not be explicitly Marxist. The 24th volume in the series focuses on Latin America. This book series is available electronically at website.
Keywords: Business & Economics -- International -- General.; Business & Economics -- Economics -- General.; Economics.; Latin America.; Capitalism.; elektronické knihy; electronic books